Antibiotic resistance profiles of coagulase-positive and coagulase-negative staphylococci from pit latrine fecal sludge in a peri-urban South African community - Beukes, Lorika S; Schmidt, Stefan (Folia microbiologica, 2018)
The aim of this study was to assess pit latrine samples from a peri-urban community in KwaZulu-Natal (South Africa) for the presence of multidrug-resistant (MDR) Staphylococcus spp. Standard procedures were used to isolate Staphylococcus spp. from pit latrine fecal sludge samples, with confirmation at genus level by polymerase chain reaction (PCR). Sixty-eight randomly selected pit latrine Staphylococcus spp. isolates were further characterized by using established disk diffusion procedures. An average Staphylococcus spp. count of 2.1 × 105 CFU per g fecal material was established using two randomly selected pit latrine samples. Of the 68-selected Staphylococcus spp. pit latrine isolates, 49% were identified as coagulase positive, 51% as coagulase negative and 65% (12 coagulase positive, 32 coagulase negative isolates) were categorized as MDR. The majority (66/68) of Staphylococcus spp. isolates displayed resistance to fusidic acid while only 5/68 isolates displayed resistance to chloramphenicol. The pit latrine samples analyzed in this study are a source of MDR Staphylococcus spp., highlighting the need for proper hygiene and sanitation regimes in rural communities using these facilities.
Keywords: Jihoafrická republika; Drug Resistance, Multiple, Bacterial; Feces; Bacterial Proteins; South Africa; mikrobiální viabilita; mnohočetná bakteriální léková rezistence; antibakteriální látky; Microbial Sensitivity Tests; koagulasa; Staphylococcus; Coagulase; DNA, Bacterial; DNA bakterií; Microbial Viability; Genes, Bacterial; Anti-Bacterial Agents; mikrobiální testy citlivosti; bakteriální proteiny; Toilet Facilities; odpadní vody; toalety; Sewage; feces; bakteriální geny